Patient-reported long-term outcome following allogeneic hematopoietic stem cell transplantation in pediatric chronic myeloid leukemia - Schleicher, Oliver; Horndasch, Annkathrin; Krumbholz, Manuela; Sembill, Stephanie; Bremensdorfer, Claudia; Grabow, Desiree; Erdmann, Friederike; Karow, Axel; Metzler, Markus; Suttorp, Meinolf (Frontiers in Oncology, 2022)
Background Pediatric CML is very rare. Before the introduction of tyrosine kinase inhibitors (TKIs), allogeneic hematopoietic stem cell transplantation (HSCT) from a donor -if available- was the standard cure attempt. Data on the long-term outcome and health-related quality of life (HRQOL) in former pediatric CML patients undergoing HSCT are lacking. Study question We investigated long-term survivors’ self-reporting to a questionnaire sent out to patients formerly enrolled in pediatric CML-HSCT trials. Methods Individuals with CML transplanted at age <18 years were identified from the German Childhood Cancer Registry database. Long-term survivors received a questionnaire based on the SF-36 and FACT-BMT asking them to self-report HRQOL issues. (Ethical vote #541_20 B, Medical Faculty, University of Erlangen-Nürnberg). Results 111/171 (64.9%) individuals survived HSCT long-term and 86/111 (77.5%) fulfilled all inclusion criteria and received the questionnaire. 37/86 (43%) participants (24 female, 13 male, median age at HSCT 12 years [range 2-18], median age at the time of the survey 29 years [range 18-43]) responded after a median follow-up period of 19 years (range 4-27) after HSCT. 10/37 (27%) participants underwent no regular medical follow-up examinations. Self-reported symptoms like chronic graft-versus-host disease (cGvHD)-associated organ impairments and conditioning regimen consequences could causatively not sharply be separated in each case. Complains comprised hypothyroidism (N=11, 30%), infertility (N=9, 24%), lung problems, dry eyes (each N=7, 19%), skin alterations (N=6, 17%), hair problems (N=4, 11%), and sexual dysfunction (N=3, 9%). 10 (27%) participants experienced 13 CML relapses after a median interval from HSCT of 31 months (range 2-93). Only one patient underwent 2nd SCT after failure of relapse treatment with TKIs. Six secondary malignancies (dysplastic melanocytic nevus and ALL, basal cell carcinoma (N=2), rhabdomyosarcoma, and thyroid carcinoma developed in 5 (13%) participants. As assessed by the SF-36 questionnaire, impaired physical health was mainly associated with cGvHD. The mental component summary score showed that also participants without cGvHD scored significantly lower than the general population. When assessed by the FACT-BMT, participants with cGvHD scored significantly lower while participants without cGvHD scored even 5 points higher than the data from controls. 18 (49%) participants considered the sequelae of HSCT an obstacle to education. Out of the total cohort, N=20 (54%), N=7 (19%), N=5 (14%), and N=4 (11%) participants worked full time, part-time, were unemployed, or had not yet finalized their education, respectively. 20 (54%) participants lived as singles, 8 (22%) lived in a partnership, 6 (16%) were married, and 3 (8%) had been divorced. Four (11%) participants reported a total number of 7 children. Conclusion This first assessment of HRQOL in former pediatric patients with CML surviving HSCT for more than two decades demonstrates self-reported satisfactory well-being only in the absence of cGvHD. Research-based on self-reported outcomes sheds light on former patients’ perspectives and provides an additional layer of valuable knowledge for pediatric and adult hematologists. Regular follow-up examinations are mandatory helping to avoid that late secondary neoplasias, CML-relapse, and disorders forming the broad range of possible long-term consequences of HSCT are not detected too late.